2022
DOI: 10.3389/fchem.2022.1030803
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in amorphous electrocatalysts for oxygen evolution reaction

Abstract: Oxygen evolution reaction (OER) has attracted great attention as an important half-reaction in the electrochemical splitting of water for green hydrogen production. However, the inadequacy of highly efficient and stable electrocatalysts has impeded the development of this technology. Amorphous materials with long-range disordered structures have exhibited superior electrocatalytic performance compared to their crystalline counterparts due to more active sites and higher structural flexibility. This review summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…It is generally observed that amorphous materials of short-range order exhibit relatively better electrocatalytic performance compared to their crystalline counterparts due to the exposure of a greater number of active sites or higher surface area. This is observed to be reported with other catalysts for different reactions as well. , The disordered amorphous surface shows better OER activity due to the exposure of a greater number of active sites and structural flexibility.…”
Section: Resultssupporting
confidence: 80%
“…It is generally observed that amorphous materials of short-range order exhibit relatively better electrocatalytic performance compared to their crystalline counterparts due to the exposure of a greater number of active sites or higher surface area. This is observed to be reported with other catalysts for different reactions as well. , The disordered amorphous surface shows better OER activity due to the exposure of a greater number of active sites and structural flexibility.…”
Section: Resultssupporting
confidence: 80%
“…[63] Investigations of amorphous materials are also significant since the defective structure offers unique sites and potentially higher surface area than crystalline counterparts. [66][67][68] The amorphous versus crystalline state of materials in relation to the OER catalytic activity is an important topic nowadays given the importance of this reaction for energy conversion devices. Some results imply that the short-range order in amorphous materials triggers the formation of specific active sites as a result of the electrochemical activation.…”
Section: Electrodementioning
confidence: 99%
“…Thereinto, FeNibased materials, especially the FeNi hydroxides, have shown excellent OER electrocatalytic activity in alkaline media. [27][28][29] Layered FeNi nanomaterials can not only provide greater electrochemcial active surface area (ECSA) and higher electrolyte accessibility, but also a more rapid gas release rate to overcome the problems of the limited exposure of active sites and the intrinsic weak conductivity of most non-precious metal catalysts. [30][31][32] For further promotion of the electrocatalytic efficiency of FeNi hydroxides, researchers have investigated several valuable strategies, such as inserting conductive materials so as to boost electron transfer capacity, 33,34 perfecting the metal coordination environment, [35][36][37] manufacturing defects to regulate electronic structures, 38,39 and exposing additional active sites through adjusting the geometry.…”
Section: Introductionmentioning
confidence: 99%